Preserving The Majapahit Cultural Heritage in Trowulan Through Innovative Indonesian Language Teaching Materials - Nurul Kholifah; Sri Wahyuni; Abdul Rani (Balai Bahasa Provinsi Bali, 2026)
This study aims to develop digital Indonesian language teaching materials incorporating Majapahit culture in Trowulan to strengthen junior high school students’ cultural literacy and character development. The study employed a Research and Development method using the 4D model (Define, Design, Develop, and Disseminate). The research subjects included Indonesian language teachers, junior high school students, and expert validators consisting of media experts and language/content experts. The research data comprised teacher and student needs analysis data, expert validation data, practicality test data, and effectiveness data. Data were collected through questionnaires, test, and validation sheets. Quantitative data were analyzed using SPSS, while qualitative data were analyzed descriptively to support interpretation. The results indicate that the developed digital teaching materials are valid based on expert evaluation and fall within the practical to very practical categories according to teacher and student responses. The materials demonstrate strengths in content relevance, ease of use, clarity of presentation, and integration of cultural values. Students also showed positive responses in terms of visual attractiveness, comprehension, and perceived usefulness. These findings suggest that integrating Majapahit culture into digital teaching materials supports contextual and meaningful Indonesian language learning. Therefore, the developed materials are feasible and effective as an alternative resource for culture-based learning aligned with the Merdeka Curriculum. AbstrakPenelitian ini bertujuan untuk mengembangkan materi ajar bahasa Indonesia digital yang menggabungkan budaya Majapahit di Trowulan untuk memperkuat literasi budaya dan pengembangan karakter siswa SMP. Penelitian menggunakan metode Penelitian dan Pengembangan menggunakan model 4D (Define, Design, Develop, and Disseminate). Subjek penelitian meliputi guru bahasa Indonesia, siswa SMP, dan validator ahli yang terdiri dari pakar media dan ahli bahasa/konten. Data penelitian terdiri dari data analisis kebutuhan guru dan siswa, data validasi ahli, data uji kepraktisan, dan data efektivitas. Data dikumpulkan melalui kuesioner, tes, dan lembar validasi. Data kuantitatif dianalisis menggunakan SPSS, sedangkan data kualitatif dianalisis secara deskriptif untuk mendukung interpretasi. Hasil penelitian menunjukkan bahwa bahan ajar digital yang dikembangkan valid berdasarkan evaluasi ahli dan termasuk dalam kategori praktis hingga sangat praktis sesuai respon guru dan siswa. Materi menunjukkan kekuatan dalam relevansi konten, kemudahan penggunaan, kejelasan penyajian, dan integrasi nilai-nilai budaya. Siswa juga menunjukkan respon positif dari segi daya tarik visual, pemahaman, dan kegunaan yang dirasakan. Temuan ini menunjukkan bahwa mengintegrasikan budaya Majapahit ke dalam bahan ajar digital mendukung pembelajaran bahasa Indonesia yang kontekstual dan bermakna. Oleh karena itu, materi yang dikembangkan layak dan efektif sebagai sumber alternatif pembelajaran berbasis budaya yang selaras dengan Kurikulum Merdeka.